2022
DOI: 10.1186/s12955-022-01985-z
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life and its association with social support among people living with HIV/AIDS receiving antiretroviral therapy in Ethiopia: a systematic review and meta-analysis

Abstract: Background People living with HIV/AIDS (PLWHA) are frequently confronted with severe social issues such as rejection, abandonment, criticism, and stigma. This would negatively affect their quality of life. Several studies have been conducted so far to assess factors affecting the health-related quality of life among people living with HIV/AIDS who are on antiretroviral therapy (ART) in Ethiopia. However, to our knowledge, there is no previous study that has summarized the results of the studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…However, the level of poor HRQoL in this study was found to be consistent with the pooled prevalence of HRQoL among general HIV-positive people in Ethiopia (45.27%) [ 36 ]. Over time monitoring of HRQoL will support HIV care and treatment practices to settle auspicious outcomes [ 23 ].…”
Section: Discussionsupporting
confidence: 84%
“…However, the level of poor HRQoL in this study was found to be consistent with the pooled prevalence of HRQoL among general HIV-positive people in Ethiopia (45.27%) [ 36 ]. Over time monitoring of HRQoL will support HIV care and treatment practices to settle auspicious outcomes [ 23 ].…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have reported that HIV infection-related health impairments, including opportunistic infections, tumors, and malnutrition will not only reduce the quality of life of PLWHA but are also be affected by factors such as sex, age, economic status, marital status, educational level, CD4 + T cell count, and viral load ( 19 21 ). Available evidence reveals that anemia is quite common in PLWHA and is significantly associated with an increased risk of premature death ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Social support is an essential buffer to stressful life events; it positively impacts an individual's physical and mental well-being, performance, creativity and competence and brings resilience when confronting stressful situations [36][37][38]. For example, an Ethiopian systematic review showed that PLHIV with good social support were four times more likely to report higher HRQoL when compared to those without (AOR = 4.01, 95% CI 3.07-5.23) [39]. Our ndings further a rm previous evidence on the intertwined relationship between social support, adherence to ART and improvement of the overall HRQoL for PLHIV [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%